Trauma and post-traumatic stress disorder in Don Delillo's Falling Man - Hashim, Hazim Adnan; Babaee, Ruzbeh (SciPress, 2015)
This article looks at 9/11 trauma and Post-traumatic Stress Disorder in Don DeLillo's Falling Man. This asserts that 9/11 has brought about not only political, social, economic and cultural consequences but also caused victims on the personal level. This paper demonstrates how Keith, the protagonist of the novel, has been affected by 9/11. In other words, this article examines Keith's traumatic experience of witnessing his close friend's death, the falling man, and escaping his own impending death in the north tower and how these horrible scenes affect Keith's perception of self. Eventually, this study concludes that DeLillo's Falling Man presents the reality of what the survivors have experienced during and after the attacks, and the complication of trauma and PTSD that turns their world topsy-turvy.